2018
DOI: 10.1128/msphere.00551-17
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Plasmodium falciparum Protein Sortilin Potentially Acts as an Escorter for the Trafficking of the Rhoptry-Associated Membrane Antigen to the Rhoptries

Abstract: The malaria parasite is a massive burden in several parts of the world. Worryingly, the parasite has become resistant to several of the drugs commonly used to treat the disease, and at this time, there is no commercial vaccine. It is therefore critical to identify new targets for the development of antimalarials. To survive in the human body, the malaria parasite needs to invade red blood cells. For this, it uses a variety of effectors stored in organelles forming a structure called the apical complex. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
2
20
1
Order By: Relevance
“…Our recent finding that PfSortilin interacted with regions of RAMA sufficient for localisation to rhoptries provided support for Sortilin's role as a protein escorter to this organelle (Hallee et al, ). To provide more direct evidence, immunofluorescence assays (IFAs) were performed with antibodies to rhoptry proteins using the PfSortilin KD and control lines grown in the presence or absence of GlcN.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Our recent finding that PfSortilin interacted with regions of RAMA sufficient for localisation to rhoptries provided support for Sortilin's role as a protein escorter to this organelle (Hallee et al, ). To provide more direct evidence, immunofluorescence assays (IFAs) were performed with antibodies to rhoptry proteins using the PfSortilin KD and control lines grown in the presence or absence of GlcN.…”
Section: Resultsmentioning
confidence: 74%
“…P. falciparum possesses a homologue of the Sortilin protein that localises to the Golgi apparatus (Hallee, Boddey, Cowman, & Richard, 2018;Koumandou et al, 2011;Krai et al, 2014), and we recently demonstrated that it interacted with regions of the glycosylphosphatidylinositol-anchored P. falciparum rhoptry-associated membrane antigen (RAMA) that were sufficient to drive a fluorescent reporter to the rhoptries which suggested that PfSortilin could act as an escorter for the trafficking of RAMA to these organelles (Hallee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for transport to Plasmodium rhoptries, no specific signals have yet been identified. However, certain regions within rhoptry proteins have been shown to be essential for localization (Ghoneim, Kaneko, Tsuboi, & Torii, 2007; Sherling et al, 2017) as well as interactions with other rhoptry proteins (Baldi et al, 2000; Hallée, Boddey, Cowman, & Richard, 2018; Morse, Webster, Kalanon, Langsley, & McFadden, 2016; Richard et al, 2009). The rhoprtry associated protein 1 (RAP1) was shown to contain a bipartite signal necessary and sufficient for trafficking to the rhoptries (Richard et al, 2009).…”
Section: An Epic Journey: From the Er To The Apical Organellesmentioning
confidence: 99%
“…This possibility has not been explored further and the rhoptry targeting signals for other rhoptry proteins remain to be identified. More recent work, has suggested that certain members of the golgi‐endosomal protein trafficking pathway, such as homologs of sortilin or VPS10p, are repurposed for targeting proteins to rhoptries (Hallée et al, 2018). The Plasmodium sortilin homolog has been shown to interact with a rhoptry protein (Hallée et al, 2018), however, more work is required to show a direct involvement of the vacuolar protein sorting pathway in directing proteins to the rhoptries.…”
Section: An Epic Journey: From the Er To The Apical Organellesmentioning
confidence: 99%